2022
DOI: 10.1136/bmjopen-2022-062388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of remote learning during the COVID-19 lockdown on children’s visual health: a systematic review

Abstract: ObjectivesIncreased exposure to digital devices as part of online classes increases susceptibility to visual impairments, particularly among school students taught using e-learning strategies. This study aimed to identify the impact of remote learning during the COVID-19 lockdown on children’s visual health.DesignSystematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Data sourcesScopus, PubMed and ScienceDirect databases from the year 2020 onwards.Eligibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
(191 reference statements)
0
12
0
Order By: Relevance
“…A systematic review of 21 articles on the effects of e-learning during the coronavirus disease 2019 (COVID-19) lockdown identified the development or exacerbation of visual problems in children, such as visual fatigue, vergence, and accommodation disturbances, associated with the increased dependence on digital devices [30]. Furthermore, a recent systematic review and meta-analysis of 45 randomized controlled trials with 4497 participants found no high-certainty evidence of reduction in visual fatigue scores or symptoms after treatment of computer vision syndrome [31].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 21 articles on the effects of e-learning during the coronavirus disease 2019 (COVID-19) lockdown identified the development or exacerbation of visual problems in children, such as visual fatigue, vergence, and accommodation disturbances, associated with the increased dependence on digital devices [30]. Furthermore, a recent systematic review and meta-analysis of 45 randomized controlled trials with 4497 participants found no high-certainty evidence of reduction in visual fatigue scores or symptoms after treatment of computer vision syndrome [31].…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic additionally impacted students’ physical health as a result of increased screen time, less physical activity, as well as unhealthy behaviors and sleep problems linked to psychological distress (Cortés-Albornoz et al, 2022; Valenzuela et al, 2022). Specifically, Cortés-Albornoz and colleagues (2022) documented that most studies in their review (19 of 21 studies) found visual health in school students to worsen during the COVID-19 pandemic, while Valenzuela and colleagues (2022) found undergraduate students to have experienced sleep problems and, interestingly, also increased sleep duration. Regarding the latter point, the authors noted that increased sleep duration may not necessarily be beneficial, as it can negatively impact time spent on school work, social relationships, and mental health.…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, school closures and remote learning affected an estimated 1.37 billion students [34]. Multiple systematic reviews and metaanalyses, albeit of predominantly Asian studies, have reported a rapid increase and/or progression in myopia among school-aged children since the pandemic onset, largely due to the increased use of digital devices during remote learning and decreased outdoor activity [35][36][37][38]. Studies have similarly reported a 1.5fold increase in astigmatism among children following school closures [39,40].…”
Section: Discussionmentioning
confidence: 99%